2012
DOI: 10.1038/sc.2012.100
|View full text |Cite
|
Sign up to set email alerts
|

Transient ischemia induces massive nuclear accumulation of SUMO2/3-conjugated proteins in spinal cord neurons

Abstract: Objectives: The objective of this study is to determine whether transient spinal cord ischemia activates small ubiquitin-like modifier (SUMO1-3) conjugation, a post-translational protein modification that protects neurons from ischemia-like conditions. Methods: Mice were subjected to 8-12 min of spinal cord ischemia and 3-24 h of recovery using a newly developed experimental model. To characterize the model, activation of stress response pathways induced after spinal cord ischemia, previously observed in other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
2
11
0
3
Order By: Relevance
“…These findings suggest that aging is associated with a decline in the capacity of cells to activate these posttranslational modifications, particularly SUMOylation and O‐GlcNAcylation. Rapid activation of both modifications has been reported in various postischemic organs 6, 8, 27, 28, 29, 30. Notably, in the present study, these were the only posttranslational modifications that showed impaired activation in both brain and kidney of aged mice.…”
Section: Discussionsupporting
confidence: 66%
“…These findings suggest that aging is associated with a decline in the capacity of cells to activate these posttranslational modifications, particularly SUMOylation and O‐GlcNAcylation. Rapid activation of both modifications has been reported in various postischemic organs 6, 8, 27, 28, 29, 30. Notably, in the present study, these were the only posttranslational modifications that showed impaired activation in both brain and kidney of aged mice.…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, it was observed that SUMO2/3 conjugation is massively increased in brains of hibernating thirteen-lined ground squirrels ( Ictidomys tridecemlineatus ) during torpor (76). Consistently, multiple studies showed a high increase of SUMO conjugation after transient ischemia in vitro and in vivo (18, 76, 79, 131, 142, 143). This raises the intriguing question about the functional contribution of SUMOylation to protect cells from damage during ischemia.…”
Section: Sumo Plays a Protective Role In Brain Ischemiasupporting
confidence: 67%
“…It is thus speculated that sumoylation may trigger such prion-like characteristics in mutant SOD1. Multiple lines of evidence indicate that SOD1 aggregate formation closely correlates with cytotoxicity in cellular models and decreased survival in model mice [1], [18]–[21], [23]. Taken together, it is assumed that the sumoylation-induced acceleration of SOD1 aggregation is linked to neurotoxicity in ALS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings provide evidence for the involvement of sumoylation in ALS pathogenesis. Since SUMOs are expressed in spinal cord neurons [20], [21], it is assumed that sumoylation may have a pathological role in motor neurons as well as astrocytes. Fei et al reported that the human SOD1 protein is sumoylated and stabilized by SUMO1, suggesting that sumoylation is linked to SOD1 aggregation [22].…”
Section: Introductionmentioning
confidence: 99%